2019
DOI: 10.1016/j.jsv.2018.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Aeroacoustic study of a wavy stator leading edge in a realistic fan/OGV stage

Abstract: The effect of sinusoidal serrations applied to the leading-edge of the vanes of a realistic fan stage is investigated using high-fidelity numerical simulations. The CFD solver PowerFLOW based on a hybrid lattice-Boltzmann/very-large-eddy-simulation model is used to compute the unsteady flow and radiated noise of the 22-in source diagnostic test fan rig of the NASA Glenn Research Center. A computational model validated for three different geometries of the outlet guide vanes with straight leading edge is used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…However, most of these papers were focused on single-wavelength serrated leading edge profiles. The noise reduction mechanism of these profiles has been investigated in detail by [6,[10][11][12][18][19][20][21] and essentially involves a reduction in the source strength everywhere along the serrated leading edge except at the root location. At this location, it has been shown that the source strength per unit edge length is identical to that of a straight edge in [11].…”
Section: A Single-wavelengthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of these papers were focused on single-wavelength serrated leading edge profiles. The noise reduction mechanism of these profiles has been investigated in detail by [6,[10][11][12][18][19][20][21] and essentially involves a reduction in the source strength everywhere along the serrated leading edge except at the root location. At this location, it has been shown that the source strength per unit edge length is identical to that of a straight edge in [11].…”
Section: A Single-wavelengthmentioning
confidence: 99%
“…Reference [21] used hybrid lattice-Boltzmann/very-large-eddy-simulation method to investigate the effect of sinusoidal serrations applied to the leading-edge of the vanes of a realistic fan stage. The results confirm the lower frequency limit established in [12] for noise reductions of at least 3dB, which shows that the Strouhal number defined relative to serration amplitude f h/U must exceed 0.2.…”
Section: A Single-wavelengthmentioning
confidence: 99%
“…Meanwhile, the data from the fluctuation pressure sensor can be transformed by the wavenumber-frequency spectrum. Then, the sound radiation can be estimated by Equation (20). Therefore, the combination of the turbulent fluctuation pressure measurement method and the reverberation method can be used to evaluate the hydrodynamic noise from the models for the whole frequency band.…”
Section: Theory Of Vibration and Sound Radiation By Flow-induced Forcementioning
confidence: 99%
“…A small plate near the leading edge of the airfoil is set to circumvent the flow separation [18]. The low-amplitude oscillating distributed surface perturbations can completely suppress the leading-edge separation bubbles [19].Casalino investigated the effect of sinusoidal serrations applied to the leading edge of the vanes of a realistic fan stage, and obtained some noise reductions when the undulation amplitude and wavelength were large enough compared to the integral scales of the impinging turbulence fluctuations [20].The listed results are mostly carried out in the aerodynamic field, and are only considered as possible references for the hydrodynamic field due to the differences between the two fields. First, the Reynolds number is larger in the water than in the air.…”
mentioning
confidence: 99%
See 1 more Smart Citation